EFFECTIVENESS OF USING SYSTEM APPLICATIONS INFORMATION ON BAZNAS MANAGEMENT (SIMBA) IN ZAKAT MANAGEMENT IN BAZNAS WEST LOMBOK DISTRICT - Ulfah, Dian Seftiana; Badriati , Baiq EL; Pratiwi, Intan Kusuma (UIN Mataram, 2023)
This study aims to determine effectiveness of using the Baznas Management Information System (SIMBA) application as well as supporting and inhibiting factors for using the Baznas Management Information System (SIMBA) application. This type of research is qualitative using a descriptive qualitative approach. The research results show that BAZNAS West Lombok Regency is able to increase the effectiveness of zakat management . However, it cannot be said to be fully effective because the timeliness when collecting reports does not match the time determined by the central BAZNAS. Supporting factors namely office facilities in the form of computers and an adequate internet network, apart from that support from central BAZNAS to continue to provide outreach and technical guidance for Admins in each region. Meanwhile, the inhibiting factor in using the SIMBA application is limited human resources or a lack of specialized personnel who are competent in the IT field so that reports cannot be completed according to the predetermined schedule